Differentiating attack-defense performance for starting and bench players during the Tokyo Olympics men`s basketball competition - Sun, W.; Chee, C.; Kok, L.; Lim, F.; Samsudin, S. (PLOS ONE, 2023)
This study aimed to explore the differences in attack-defense performance between the top and bottom teams for starting and bench players during the Tokyo Olympics men`s basketball competition, to determine the relationship between the attack-defense performance of starting and bench players and the final competition rankings, as well as with each performance indicator. The rank-sum ratio (RSR) comprehensive evaluation was employed to describe the attack-defense performance of starting and bench players. Additionally, an independent sample t-test, Spearman Rho Correlation, and Pearson Correlation were conducted to test the differences and relationships between the various variables at a 0.05 level of significance, respectively. The results indicated that the top four teams showed significant differences in the attack-defense performance of their starting players compared to the bottom four teams (p = 0.021), mainly in terms of 3-point shooting percentage (p = 0.042) and free throw shooting percentage (p = 0.044). Besides that, the attack-defense ranks of both starting players (p = 0.004, r = 0.757) and bench players (p = 0.020, r = 0.658) had a significant correlation with the final rankings. Points per game, 2-point field goal percentage, and assists had a statistically significant (p<0.01) and strong positive correlation (0.70<r<0.90) with the attack-defense performance of both starting and bench players. 3-point field goal percentage, offensive rebounds, defensive rebounds, steals, and blocks were the technical indicators that distinguish starting from bench players. In conclusion, one of the common characteristics of the top national basketball teams was the strong attack-defense ability of the starting players. It is recommended that coaches select players with stronger 3-point shooting ability and more accurate free-throw shooting into the team`s starting rotation.